Hypothermia treatment ameliorated cyclin-dependent kinase 5-mediated inflammation in ischemic stroke and improved outcomes in ischemic stroke patients - Hongwei Sun; Juan Cai; Shiqi Shen; Xiaohui Ren (Clinics, 2019)
OBJECTIVES: The inflammatory response is a key mechanism of neuronal damage and loss during acute ischemic stroke. Hypothermia has shown promise as a treatment for ischemic stroke. In this study, we investigated the molecular signaling pathways in ischemic stroke after hypothermia treatment. METHODS: Cyclin-dependent kinase 5 (CDK5) was overexpressed or silenced in cultured cells. Nuclear transcription factor-κB (NF-κB) activity was assessed by measurement of the luciferase reporter gene. An ischemic stroke model was established in Sprague-Dawley (SD) rats using the suture-occluded method. Animals were assigned to three groups: sham operation control, ischemic stroke, and ischemic stroke + hypothermia treatment groups. Interleukin 1β (IL-1β) levels in the culture supernatant and blood samples were assessed by ELISA. Protein expression was measured by Western blotting. RESULTS: In HEK293 cells and primary cortical neuronal cultures exposed to hypothermia, CDK5 overexpression was associated with increased IL-1β, caspase 1, and NF-κB levels. In both a murine model of stroke and in patients, increased IL-1β levels were observed after stroke, and hypothermia treatment was associated with lower IL-1β levels. Furthermore, hypothermia-treated patients showed significant improvement in neurophysiological functional outcome. CONCLUSIONS: Overall, hypothermia offers clinical benefit, most likely through its effects on the inflammatory response.